Bibliometric Analysis of Psychomotricity Research Trends: The Current Role of Childhood - Ángel Denche-Zamorano; María Mendoza-Muñoz; Sabina Barrios-Fernandez; José A. Parraca (MDPI AG, 2022)
Psychomotricity is a wide broad term, which encompasses different bodily action approaches to support children and adolescents to achieve their highest potential. A search on the Web of Science (WoS) Core Collection database was performed on this topic, using traditional bibliometric laws. Finally, 118 publications (112 articles and 6 reviews) documents were found. Annual publications presented an exponentially growing trend (R2 = 84.7%). Spain was the most productive country/region worldwide. Paola Magioncalda, Matteo Martino y Víctor Arufe Giraldez were highlighted as the most prolific co-authors. "Retos Nuevas Tendencias en Educación Física, Deporte y Recreación" was the most productive journal and the "International Journal of Environmental Research and Public Health", was the second most productive; the third in the list was the most productive in the JCR ranking. Thus, research on psychomotricity is experiencing exponential growth, causing this topic to generate great interest among researchers, publishers and journals. The most cited paper was "Neurocognitive Effects of Alcohol Hangover". The author keywords that were first raised together with psychomotricity were related to rehabilitation and psychomotor development, while the current trend was focused on physical activity and early childhood education.